2007
DOI: 10.1063/1.2713170
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the dynamics of polar nanoregions and temperature evolution of central peaks in Pb[(Zn1∕3Nb2∕3)0.91Ti0.09]O3 ferroelectric relaxors

Abstract: Acoustic properties of Pb͓͑Zn 1/3 Nb 2/3 ͒ 0.91 Ti 0.09 ͔O 3 have been investigated in a wide temperature range. The sound velocity of acoustic phonons showed a deviation from its high-temperature linear behavior at the Burns temperature T B ϳ 730 K. Upon cooling, acoustic properties exhibited significant changes at about 550 K in polarization state and width of the central peak in addition to changes in frequency and damping of acoustic phonons. This finding suggests that, besides T B , another intermediate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 22 publications
4
44
0
Order By: Relevance
“…22͒ and recent light scattering studies on PZN-9%PT crystal. 16 It is about 100 K below this temperature where the quasielastic CP becomes more prominent as observed in PLZT relaxor 23 and in the present case also. A similar trend of the CP has also been reported for PMN-32%PT crystal by neutron scattering experiments 24 and associated with the dynamical evolution of PMRs.…”
Section: ͑Pmn-xpt͒mentioning
confidence: 68%
See 1 more Smart Citation
“…22͒ and recent light scattering studies on PZN-9%PT crystal. 16 It is about 100 K below this temperature where the quasielastic CP becomes more prominent as observed in PLZT relaxor 23 and in the present case also. A similar trend of the CP has also been reported for PMN-32%PT crystal by neutron scattering experiments 24 and associated with the dynamical evolution of PMRs.…”
Section: ͑Pmn-xpt͒mentioning
confidence: 68%
“…15 Recent light scattering studies on PZN-xPT crystal have indicated the existence of an intermediate temperature at which the coupling between the PMRs and acoustic modes becomes more visible. 16 In this letter we present a direct evidence of mode coupling that gives rise to line shape anomalies in the light scattering spectra of the PMN-33%PT ͓001͔-oriented single crystal using the high-resolution micro-Brillouin scattering.…”
Section: ͑Pmn-xpt͒mentioning
confidence: 99%
“…In relaxor ferroelectrics, CP that begins to appear well above T m is attributed to the relaxational dynamics of PNRs. 5,7 As shown in Fig. 7, the decrease in the width and increase in the integrated intensity of CP indicates critical slowing down of the relaxation time and increase in the correlations between the PNRs with decrease in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…2 Extensive studies on the dynamical aspects of PNRs have been carried out in prototype RFEs such as Pb(Mg 1/3 Nb 2/3 )O 3 (PMN) and other related systems through neutron and light scattering studies. [3][4][5][6][7][8][9] Brillouin scattering studies in these systems directly revealed the dynamical features of the PNRs such as the slowing down of their relaxation time and the coupling between the polarization fluctuations and acoustic phonon modes through the appearance of central peak (CP) and softening of the acoustic phonon mode. [6][7][8][9] This paper focuses on micro-Brillouin scattering studies on the dynamical aspects of PNRs in partially ordered Pb(Sc 1/2 Ta 1/2 )O 3 (PST) without any Pb vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…12-21,30-35 On further cooling, a smeared frequency dependent temperature maximum of the dielectric response occurs near T m and, slightly below T m the freezing occurs at the freezing temperature T f , similar to polar-glass phases. [36][37][38][39] In contrast to these observations, one finds that AE studies [12][13][14][15][16][17][18][19]22,23,[25][26][27][28][29][30] show extremely sharp singularities at T d and T * , which is sometimes related to changes of the thermal expansion. 40 While this behavior is unlikely when the anomaly is close to the Widom line and far away from the transition point, 41 we will also show in this paper that AE persists even without any changes in thermal expansion.…”
mentioning
confidence: 58%